PERSEPSI PESERTA DIDIK SEKOLAH DASAR TERHADAP PEMBELAJARAN BERBASIS PEDAGOGICAL TECHNOLOGICAL CONTENT KNOWLADGE DALAM PENINGKATAN LITERASI MEMBACA - Amaliya Islami Nurlaili; Radeni Sukma Indra Dewi; Amaliya Islami Nurlaili (Universitas Negeri Malang, 2024)
This article is motivated by the importance of students' reading literacy skills, which can be enhanced through TPACK-based learning. The research aims to explore students' perceptions of pedagogical technology-based learning containing knowledge to improve reading literacy. This study focused on upper-class students, specifically in class IV, with 27 students participating as respondents. The research employs a qualitative approach with descriptive analysis methods. Techniques include questionnaires and document studies, while data analysis involves a literature review. The results reveal that 85.18% of students favor TPACK-based learning content, and 88.88% of students demonstrate comprehension of learning material presented using the TPACK approach. Thus, this research underscores the effectiveness of the TPACK approach in enhancing students' reading literacy skills.